The Effect of Fatalistic Tendency in Individuals on Attitudes Toward Epilepsy Patients - Öznur Adadioğlu; Ahmet Seven; Metin Yıldız (Brain and Behavior)
ABSTRACT Objective This study was conducted to determine the effect of fatalistic tendency on attitudes toward epilepsy patients. Methods The study was conducted between August 17 and October 1, 2022 in a family health center in Sakarya province in western Türkiye. The sample consisted of 479 adults. Data were collected in descriptive information forms, the fatalism tendency scale and the epilepsy attitude scale. The data were analyzed using SPSS 22.0, AMOS V 24.0, and G*Power 3.1 statistical package programs. Results Results showed that the model built according to the hypotheses was compatible, and the model fit indices χ2/Sd = 1.857, RMSEA = 0.04, CFI = 0.98, GFI = 0.99, AGFI = 0.97, and IFI = 0.98 were within the desired limits. Structural equation modeling to determine the effect of fatalistic tendency on attitudes toward epilepsy revealed that fatalistic tendency affected the attitudes toward epilepsy patients (β = 0.87, p < 0.05). Conclusion In our study, as the fatalistic tendency of individuals increased, their negative attitudes toward epilepsy patients increased. Longitudinal studies on attitudes toward epilepsy patients are recommended.